Single and multi-dimensional optimal auctions: a network approach - Alexey Malakhov; Rakesh V. Vohra (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2004)
This paper highlights connections between the discrete and continuous approaches to optimal auction design with single and multi-dimensional types. We provide an interpretaion of an optimal auction design problem in terms of a linear program that is an instance of a parametric shortest path problem on a lattice. We also solve some cases explicitly in the discrete framework.
Keywords: C61; C70; D44; 330; Auctions; Networks; Linear Programming; Auktionstheorie; Netzwerk; Mathematische Optimierung